(untitled) (Journal of the Management Sciences, 2024)
Cash management is essential to the survival, growth and performance of any manufacturing industry. This study thus examined cash management and the performance of Jezco Oil Ltd, Awka, Anambra State. The specific objectives are; to determine the level of relationship that exists between treasury bill and production cost; to examine the degree of relationship that exists between saving bond and production volume; to evaluate the extent of relationship that exists between certificate of deposit and operation efficiency. Survey research design was adopted for this study, the population of the study comprises 70 employees both the management, junior and senior staff in various departments in Jezco Oil Ltd Awka. A sample size of 59 were selected randomly for this study. Data was collected with use of primary source which was obtained from respondents through a structured questionnaires formulated by the researcher. Data was analyzed with Pearson product moment correlation through simple linear regression with SPSS version 23. The findings of the study show that treasury bill has significant effect on production cost with a (R-square of 0.950, at p-value < .001), there is a significant effect of saving bound on production volume (R-square of 0.958, at p-value < .001), certificate of deposit has a significant effect on operation efficiency (R-square of 0.939, at p-value < .001). The study conclude that cash management has a significant effect on manufacturing industry performance. The study recommends that Companies should prioritize effective cash management strategies: Given the significant impact of cash management factors on production costs, it is crucial for manufacturing companies to implement effective strategies to manage their cash flow.